Provincializing empire : omi merchants in the Japanese transpacific diaspora - Uchida, Jun (Oakland, California : University of California Press, 2023)
"Provincializing Empire explores the global history of Japanese expansion through a regional lens. It rethinks the nation-centered geography and chronology of empire by uncovering the pivotal role of expeditionary merchants from Omi (present-day Shiga Prefecture) and their modern successors. Tracing their lives from the early modern era, and writing them into the global histories of empire, diaspora, and capitalism, Jun Uchida offers an innovative analysis of expansion through a story previously untold: how the nation's provincials built on their traditions to create a transpacific diaspora that stretched from Seoul to Vancouver, while helping shape the modern world of transoceanic exchange"--
The rise of Ōmi shōnin as diasporic traders-- At the nexus of colonialism and capitalism in Hokkaido-- A vision of transpacific expansion from the periphery-- The production of global Ōmi shōnin-- The “gōshū zaibatsu” in Japan's cotton empire-- Ōmi merchants in the colonial world of retail-- A Shiga immigrant diaspora in Canada.
"Open access edition funded by the National Endowment for the Humanities."
Includes bibliographical references and index.
AAL
Donated by Embassy of Japan in Bangladesh, Read Japan Project 2025, The Tokyo Foundation, supported by The Nippon Foundation.
Keywords: Merchants -- Japan -- Shiga-ken -- History; Japan -- Commerce -- History